Malaysian Institutional investors’ Annual Reports Information Needs (Malaysian Management Journal, 1995)
This paper examines annual report information needs of Malaysian institutional investors. Data were colleted from a sample of 286 institutions (comprising government agencies and private industries) through questionnaires, and were analysed to test for differences and relationship in the extent of usage and perceived importance of annual reports in Malaysia. The result indicate some significant differences in the extent of usage and in the perceived importance of items in annual reports between institutional investors.